The Role of Talent Management on Strategic Performance Reinforcement A field research on some of Sumer's university colleges. - الناصري, طارق كاظم (Journal of Economics and Administrative Sciences, 2018)
In this research we have tackled the role of Talent management (as a private variable) within (the Talent attraction, the Talent management performance, Talent development and Talent retention) on strategic performance reinforcement ( accredited variable) within its dimensions ( financial perspective, costumer perspective, internal operations perspective and learning and development perspective). The research conducted on sample of some college teachers from two of Sumer's colleges. The research problem represented by the broad organization's competition as well as universities; which led these colleges to investigate it's skillful human staff to meet it's strategic performance.  To meet the aims of this research, two hypothesis have been tackled; and eight variables depending upon a questionnaire collected by 50 college teacher Distributors on college Administration and Economics  and Basic Education college/ Sumer university. The data have been analyzed using SPSS computer program to find out ( rational mean, normative deflection, correlation factor (Spearman)…). The results shows that the correlation factor between Talent  management and the strategic performance is very clear and have a physical indication. In which it clarifies the fact that the Talent management role on strategic performance. Finally, the research recommending the necessity of using developed approach of skillful human role  management, depending upon clear (countable and quant table) and measurements, to be measured and in continuous supervision of skillful human by some specialized  commissions, and comparing them with other colleges.